Implant-supported hybrid prosthesis: Conventional treatment method for borderline cases - Egilmez, Ferhan (Eur J Dent, 2015)
An implant-supported hybrid prosthesis is an acrylic resin complete fixed dental prosthesis and supported by implants might be a solution in extreme cases that the need of the restoration for esthetics, function, lip support, and speech. This clinical report aims to present the esthetic and functional prosthetic rehabilitation of three borderline cases with implant-supported hybrid prostheses. Patient 1 (62-year-old man) and Patient 2 (61-year-old man) presented a chief complaint of a compromised esthetic. After clinical evaluations, in Patient 1, 8 implants in the maxilla and 7 implants in mandibula were observed. Patient 2 had 7 implants in the maxilla and 7 implants in mandibula, which were previously placed. The intra-arch dimension of both patients was excessive and an insufficient peri-oral soft tissue support was observed. Patient 3 was a 61-year-old man had 2 implants with a history of previously implanted graft infection and implant loss on his maxillary posterior jaw. An excessive intra-arch dimension was observed in clinical examination. In addition, massive bone defect and insufficient soft tissue support were examined. In all patients, implant-supported hybrid prostheses were successfully performed. The clinical and radiologic findings were satisfactory. After 3 years of follow-up, no functional, phonetic, or esthetic problems with the restorations were noted. These case reports suggest that implant-supported hybrid prostheses can be a reliable alternative treatment procedure when a porcelain-fused metal fixed restoration does not satisfy a patient's requirements for esthetics, phonetics, oral hygiene, and oral comfort.